2022
DOI: 10.1155/2022/6534126
|View full text |Cite|
|
Sign up to set email alerts
|

Single-Cell Sequencing Revealed Pivotal Genes Related to Prognosis of Myocardial Infarction Patients

Abstract: Objectives. Myocardial infarction (MI) is a common cardiovascular disease. Histopathology is a main molecular characteristic of MI, but often, differences between various cell subsets have been neglected. Under this premise, MI-related molecular biomarkers were screened using single-cell sequencing. Methods. This work examined immune cell abundance in normal and MI samples from GSE109048 and determined differences in the activated mast cells and activated CD4 memory T cells, resting mast cells. Weighted gene c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 47 publications
0
5
0
Order By: Relevance
“…Currently, the levels of myocardial enzyme (CKMB) and cardiac troponin I (cTnI) are still the gold standards for the clinical diagnosis of AMI, but they are not specific for AMI. Previous studies indicated that patients with heart failure, chronic kidney disease, and septicemia also have elevated cardiac troponin I (cTnI) levels, which may lead to false-positive results in AMI diagnosis [7,8]. Current studies have suggested that the circulating miRNAs, such as miRNA-499, miRNA-22, miR-223-3p, and miR-483-5p, could be used as potential biomarkers of AMI [9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…Currently, the levels of myocardial enzyme (CKMB) and cardiac troponin I (cTnI) are still the gold standards for the clinical diagnosis of AMI, but they are not specific for AMI. Previous studies indicated that patients with heart failure, chronic kidney disease, and septicemia also have elevated cardiac troponin I (cTnI) levels, which may lead to false-positive results in AMI diagnosis [7,8]. Current studies have suggested that the circulating miRNAs, such as miRNA-499, miRNA-22, miR-223-3p, and miR-483-5p, could be used as potential biomarkers of AMI [9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…The initial step of the analysis involved preprocessing the scRNA-seq data using the “Seurat” package. This preprocessing encompassed several procedures, including assessing the proportion of mitochondrial genes using the PercentageFeatureSet function and conducting correlation analysis to explore relationships between sequencing depth, mitochondrial gene sequences, and total intracellular sequences [ 35 ].…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, CXCL10 and CXCL12 have leukocyte-independent mediatory effects, directly modulating CFs ( Chen and Frangogiannis, 2021 ). Additionally, single-cell sequencing has found different immune cell abundance (resting and activated mast cells, activated CD4 memory T cells) and high expression of chemokines in MI patients (CCL3, CXCL3, CXCL8, and CXCL16 in CD1C-CD141-dendritic cells and CCL4 and CCL5 in natural killer cells) ( Zhou et al, 2022 ).…”
Section: Pathophysiology Of Post-mi Cardiac Fibrosismentioning
confidence: 99%